Panorama Results Through the Years - Vignale, Ralph E. (Pan Evolution)
A list of past Panorama results, including the name of the band, tune of choice, composer and arranger from 1963 to 1981. Also, a listing of pan events , dates, the venues and prices for 2004.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Panorama (Musical festival); Steel bands (Music) -- Trinidad and Tobago -- History